Problemas en torno a la filosofía de la educación - Darós, William Roberto (Sapientia, 2010)
This article studies the complexity of a philosophy of education, either from the point of view of what a philosophical system is already or due to the complexity of the human being and society. Secondly, the article considers the complexity contained in the concept of education and the difficulty of outlining it in its definition and in an educational philosophical theory. The author, in turn, proposes a possible definition of education which is integral and comprehensive, searching to improve a biased vision, based on an almost exclusively intellectual development.